Harnessing desert resources: a comparative study of microgreens growth, nutrient dynamics, and performance in desert sand and rockwool - Nishanth, Drishya; Somanathan Nair, Chythra; Manoharan, Ramya; Subramanian, Radhakrishnan; Ahmed, Zienab F. R.; Jaleel, Abdul (Frontiers in Plant Science, 2025)
Food security in arid regions, such as the United Arab Emirates (UAE), is a significant challenge due to harsh environmental conditions such as low rainfall, high temperatures, and low-quality soil. These factors limit agricultural productivity and compromise stability. In such regions, where desert dunes are abundant, using sand as a plant growth medium presents unique opportunities to reduce reliance on expensive, synthesized substrates like rockwool, which have a larger carbon footprint. Using desert sand as an alternative to growing low-input, yet nutrient-rich crops, such as microgreens, offers a promising solution for sustainable food production in arid regions. This study aimed to assess the feasibility and effectiveness of using desert sand as a growth medium for cultivating six different types of microgreens in comparison to conventional rockwool medium (control), with a focus on their growth performance and nutritional quality. Six microgreens—Fenugreek (Trigonella foenum-graecum L.), Mustard (Brassica juncea L.), Ajwain (Trachyspermum ammi L.), Alfalfa (Medicago sativa L.), Arugula (Eruca sativa L.), and Thyme (Thymus vulgaris L.)—were grown in two different media: desert sand and rockwool (control). Growth parameters (shoot length, root development), yield (fresh and dry weight), and nutritional attributes (chlorophyll, carotenoids, total phenols, ascorbic acid, and antioxidant activity) were measured and compared across treatments. The results demonstrated that microgreens grown in desert sand outperformed those grown in rockwool, exhibiting longer shoot lengths, increased root development, and higher yields. Alfalfa and fenugreek recorded the highest fresh and dry weights. Additionally, the type of media had a significant impact on the phytochemical content. Microgreens grown in sand showed higher levels of total phenols, antioxidants, and ascorbic acid—particularly in ajwain and thyme—while chlorophyll and carotenoid content showed minor variations across both media. The superior performance of microgreens in desert sand can be attributed to the mineral content of sand, especially calcium, as confirmed by ICP-MS analysis. Desert sand emerges as a sustainable and cost-effective alternative to non-biodegradable substrates like rockwool, offering a viable solution for the cultivation of nutrient-rich microgreens in arid regions.